Daya Hambat NaCl terhadap Pertumbuhan Staphylococcus aureus - Amalia Amalia; Ratih Dewi Dwiyanti; Haitami Haitami (Medical Laboratory Technology Journal, 2016)
Staphylococcus aureus is a pathogenic bacterial that causes infectious disease and human poisoning through enterotoxin produced by the bacteria. Salt or sodium chloride is used by human for food preservation process because it can inhibit the growth of bacteria, especially Staphylococcus aureus. The purposes of the study were to determine the effect of NaCl in media on the growth of Staphylococcus aureus and determine the effective concentration of NaCl. The type of research used in this study was true experiment posttest only control group design. Samples were prepared in 5 NaCl concentrations, they were 10%, 15%, 20%, 25% dan 30%. The study conclusion was there were effects of NaCl addition to the media on the growth of Staphylococcus aureus with a significance value of 0.000 (